Extravagant in the Koran - اسماء عباس جاسم (College of Education for Women, 2019)
This research deals with a disease of the diseases our Muslim society, which works in the body operate deadly epidemics in the bodies and of bodies, but it is extravagant; has spread and rampant in our uncle everything which threatens significant damage in this life and the afterlife, as well as that it shows that Alasirafla limited to extravagant in wasting money and with this blessing should not have, and not be used as created him . Excessive linked to all aspects of life, physical and moral it has many pictures and various forms, came at the forefront of research and five sections: The first topic: the meaning of truth and extravagant. The second topic: Photos extravagant reprehensible contained in the Koran. The third topic: defamation extravagant and wasteful in the Koran . Section IV: penalty extravagant and wasteful in this world and the afterlife. Section V: extravagant effects on the individual and society. The conclusion stating the most important findings through research.